Silencing of LncRNA KCNQ1OT1 confers an inhibitory effect on renal fibrosis through repressing miR-124-3p activity. Issue 4 (1st April 2022) - Hao, Jian; Zhou, Yun; Yu, Weimin; Li, Hui; He, Dandan
ABSTRACT: LncRNA have been increasingly shown that plays pivotal roles in the development of various diseases, including renal fibrosis. Nevertheless, the pathological function of Long non-coding RNA KCNQ1OT1 (KCNQ1OT1) in the renal fibrosis remains obscure. Unilateral ureteral obstruction (UUO) was used to induce renal fibrosis. We detected the expression levels of KCNQ1OT1 in the TGF-β1-induced HK-2 cells via RT-qPCR analysis. The functions of KCNQ1OT1 on the progression of renal fibrosis were examined by CCK-8, EdU, dual-luciferase reporter, and immunofluorescence analyses. In the present study, we found that sh-KCNQ1OT1 obviously attenuated UUO-induced renal fibrosis. Moreover, production of extracellular matrix (ECM), including α-SMA and Fibronectin levels, was significantly increased in kidney and HK-2 cells after UUO or TGF-β stimulation. Knockdown of KCNQ1OT1 inhibited cell proliferation and inhibits the α-SMA and Fibronectin expression of TGF-β1-induced HK-2 cells. In addition, bioinformatics analysis and dual-luciferase reporter assay indicated that miR-124-3p was a target gene of KCNQ1OT1. Mechanistically, silencing miR-124-3p abolished the repressive effects of KCNQ1OT1 on TGF-β1-induced HK-2 cells. In conclusion, KCNQ1OT1 knockdown plays an anti-fibrotic effect through promotion of miR-124-3p expression in renal fibrosis, which provides a promising therapeutic target for the treatment of renal fibrosis. Graphical Abstract: uf0001